Reliability of pulse photoplethysmography sensors: Coverage using different setups and body locations - Armañac-Julián, Pablo; Kontaxis, Spyridon; Rapalis, Andrius; Marozas, Vaidotas; Laguna, Pablo; Bailón, Raquel; Gil, Eduardo; Lázaro, Jesús (Frontiers in Electronics, 2022)
Pulse Photoplethysmography (PPG) is a simple and economical technique to obtain cardiovascular information. In fact, PPG has become a very popular technology among wearable devices. However, the PPG signal is well-known to be very vulnerable to artifacts, and a good quality signal cannot be expected for most of the time in daily life. The percentage of time that a given measurement can be estimated (e.g., pulse rate) is denoted coverage (C), and it is highly dependent on the subject activity and on the configuration of the sensor, location and stability of contact. This work aims to quantify the coverage of PPG recorded at different places of the body, and under different stress conditions, using the electrocardiogram as reference. We report the coverage for estimating Pulse Rate (PR), but also for estimating Pulse Arrival Time (PAT) and Pulse Amplitude Variability (PAV). Three different datasets are analyzed for this purpose, consisting of a tilt-table test, an acute emotional stress test and a heat stress test. The datasets include 19, 120 and 51 subjects, respectively, with PPG at finger and at forehead for the first two datasets, and at earlobe, in addition, for the latter. C ranges from 70% to 90% for estimating the PR. Regarding the estimation of PAT, C ranges from 50% to 90%, and this is very dependent on the PPG sensor location, PPG quality and the fiducial point (FP) chosen for the delineation of PPG. In fact, the delineation of the FP is critical in time for estimating derived series such as PAT, due to the small dynamic range of these series. For PAV estimation, C rates are between 70% and 90%. In general, lower C rates have been obtained for the PPG at forehead. No different C has been observed between using PPG either at finger or at earlobe. However, different C rates are obtained, using the same PPG signal, depending on the FP chosen for delineation. Lower C is reported when using the apex point of the PPG, instead of the maximum flow velocity or the basal point, with a difference from 1% to even 10%.